2003
DOI: 10.1291/hypres.26.459
|View full text |Cite
|
Sign up to set email alerts
|

Variation near the Region of the Lipoprotein Lipase Gene and Hypertension or Blood Pressure Levels in Chinese.

Abstract: Essential hypertension (EH) is a common late-onset disease that exhibits complex genetic heterogeneity. Human lipoprotein lipase (LPL) is a rate-limiting enzyme that regulates the catabolism of triglycerides (TG) and chylomicrons (CM). Since dyslipidemia is a common finding in hypertensive patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…In our recent linkage study involving 148 hypertensive families, a linkage of SBP and DBP with the marker D8S261 in the LPL gene region was found by quantitative trait linkage analysis ( p 0.002 for SBP, and p 0.04 for DBP). This result indicated that the LPL gene and adjacent region might contribute to individual BP variation in the Chinese population (13,14). In the present association study, we followed up this finding by investigating whether variants of the LPL gene were responsible for BP variability in the Chinese population.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In our recent linkage study involving 148 hypertensive families, a linkage of SBP and DBP with the marker D8S261 in the LPL gene region was found by quantitative trait linkage analysis ( p 0.002 for SBP, and p 0.04 for DBP). This result indicated that the LPL gene and adjacent region might contribute to individual BP variation in the Chinese population (13,14). In the present association study, we followed up this finding by investigating whether variants of the LPL gene were responsible for BP variability in the Chinese population.…”
Section: Discussionmentioning
confidence: 76%
“…Sass and colleagues showed an association between the G447 allele and both lower SBP and pulse pressure (PP) levels in females in the Stanislas cohort (11), and Clee et al found that both male and female carriers of the S447X variant had decreased diastolic blood pressure (DBP) and SBP (12). Moreover, our previous linkage study suggested that the LPL gene and adjacent genomic region might contribute to individual BP variation in the Chinese population (13,14). We therefore performed the present association study by screening variants in the LPL gene and assessing their association, both individually and as haplotypes, with essential hypertension (EH) in a northern Chinese Han population.…”
Section: Introductionmentioning
confidence: 99%
“…LPL is one of the candidate genes of dyslipidemia (Hoffer et al, 1998;Julien et al, 1998;Pillarisetti and Saxena, 2003;Pruneta-Deloche et al, 2005) and hypertension (Williams et al, 1994;Yang et al, 2003b;Li et al, 2004;Chen et al, 2005) because its gene product is a major regulator of triglyceride clearance in the blood. LPL catalyzes the hydrolysis of triglycerides of circulating chylomicrons and VLDL, excesses of which are the potent causes of both disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in locus intron 6 of LPL gene (Oka et al, 1989, Zuliani & Hobbs, 1990 lead to hypertriglyceridemia, dyslipidemia leading to various disorders as coronary artery disease, hypertension and obesity. The association betweeen hypertension and the LPL locus (8p22) was reported by several studies (Chen et al, 2005, Yang et al, 2003. Significant evidence for linkage of systolic BP, but not diastolic BP has been associated with LPL locus located on the short arm of chromosome 8 (8p22) (Du-An et al, 1992).…”
Section: Lipoprotein Lipasementioning
confidence: 91%